PEMBELAJARAN MEMBACA PERMULAAN MELALUI PERMAINAN BAHASA SISWA KELAS I SDN BULAKREJO MADIUN - Nur Samsiyah; Apri Kartika Sari; Yeni Sulistyaningrum (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2013)
Early reading is a stage of learning reading for elementary school students of early grades. They learn to acquire the reading skill and techniques tosuccessfully decode passages. Learning atmosphere should be created through the language plays for reading. It goes with their characteristic of enjoying playing, Language playsplay a vital role to support their cognitive and social development. The current study aims to describe the process as well as the results of early reading through a language play at early grades of elementary school. Qualitatively approached, the current study involves participants of the first graders of the elementary school SDN BulakrejoMadiun. Data were collected through observation and documentation. Results show: (1) high achievement of average 80.7; (2) high enthusiasm specifically on the play batuloncatan (stepping stone); (3) the play could be carried out in and out of classroom and increasing their interest; and (4) headmaster, teachers and students appreciate the learning reading through the play.